Pola Pemberdayaan Masyarakat Melalui Kampung Reforma Agraria di Desa Mekarsari, Kecamatan Panimbang, Kabupaten Pandeglang - Arnowo, Hadi (Tunas Agraria, 2025)
The Agrarian Reform Village in Mekarsari Village is the result of the implementation of a post-asset management access management program through community empowerment. However, there are a number of problems, such as a lack of infrastructure, inadequate assistance with agricultural production facilities, and limited access to capital. This research aims to develop an effective pattern of community empowerment after asset structuring. The research method used is descriptive qualitative with primary data from interviews with the community, field observations, and secondary data. The research results show that the government has built simple housing and road infrastructure, although it is still inadequate. Support in the form of agricultural production facilities has been provided, while access to capital is facilitated through a cheap credit program by Permodalan Nasional Madani. Based on data analysis, the community empowerment pattern was formulated into three segments: planning, implementation, and evaluation, with activities involving community participation. The Agrarian Reform Task Force has a strategic role in coordinating activities to ensure program sustainability. This pattern is expected to be able to answer challenges and improve the welfare of the community in the Agrarian Reform Village.   Kampung Reforma Agraria di Desa Mekarsari,  merupakan hasil implementasi program penataan akses pasca penataan aset melalui pemberdayaan masyarakat. Namun, terdapat sejumlah permasalahan seperti kurangnya infrastruktur, minimnya pendampingan, kurang memadainya bantuan sarana produksi pertanian, serta terbatasnya akses permodalan. Penelitian ini bertujuan untuk menyusun pola pemberdayaan masyarakat yang efektif pasca penataan aset. Metode penelitian yang digunakan adalah kualitatif deskriptif dengan data primer dari wawancara dengan masyarakat, pengamatan lapangan, serta data sekunder. Hasil penelitian menunjukkan bahwa pemerintah telah membangun perumahan sederhana dan infrastruktur jalan meski masih kurang memadai. Dukungan berupa sarana produksi pertanian telah diberikan, sedangkan akses permodalan difasilitasi melalui program kredit murah oleh Permodalan Nasional Madani. Berdasarkan analisis data, pola pemberdayaan masyarakat dirumuskan dalam tiga segmen: perencanaan, pelaksanaan, dan evaluasi, dengan kegiatan yang melibatkan partisipasi masyarakat. Gugus Tugas Reforma Agraria memiliki peran strategis dalam mengoordinasikan kegiatan untuk memastikan keberlanjutan program. Pola ini diharapkan mampu menjawab tantangan dan meningkatkan kesejahteraan masyarakat di Kampung Reforma Agraria.